PENGARUH INOKULASI SEJUMLAH ISOLAT AZOSPIRILLUM TERHADAP PERTUMBUHAN DAN SERAPAN PUPUK N PADA TANAMAN JAGUNG - Gandanegara, S; Slamet, S; Idawati, Idawati; Lina, M (Research Center for Biology-Indonesian Institute of Sciences, 2002)
Two greenhouse experiments had been conducted to study the effect of inoculation of some Azospirillum isolates on maize growth in sand culture and sterilized soil. In the first experiment some growth parameters were used, i.e., root length and root surface area, dry weight of root, shoot, and shoot length. Inoculation enhanced plant growth, as shown by increased of all plant growth parameters. Root length and root surface area were sensitive parameter and could be used for evaluating the effect of inoculation. The best plant perfomance achieved by inoculation with Azospirillum isolates Btl No. 8 and No. 11 and with the increase of plant biomass 24 and 53% over control, respectively. In the second experiment, six selected Azospirillum isolates were evaluated on growth, N uptake, and N contribution15 in maize plants. N isotope dilution method was used to measure the N contribution from fertilizer. Uninoculated control plants showed low dry weight and contribution from N fertilizer, 3.09 gram and 10.84%. Inoculation increased mineral nutrition expressed in higher N plant yield and N contribution from fertilizer. N plant yield ranging from 147 to 189 mg N as compared to 134 mg N in control plants. The high contribution of N fertilizer (13.21-14.35 %) achieved by inoculation with Azospirillum isolates No. 6, 7, 8, and RDCB Az 1